Indonesian Landforms and Plate Tectonics - Verstappen, Herman Th. (Indonesian Journal on Geoscience, 2010)
DOI:Â 10.17014/ijog.v5i3.103The horizontal configuration and vertical dimension of the landforms occurring in the tectonically unstable parts of Indonesia were resulted in the first place from plate tectonics. Most of them date from the Quaternary and endogenous forces are ongoing. Three major plates â the northward moving Indo-Australian Plate, the south-eastward moving SE-Asian Plate and the westward moving Pacific Plate - meet at a plate triple-junction situated in the south of New Guineaâs Birdâs Head. The narrow North-Moluccan plate is interposed between the Asia and Pacific. It tapers out northward in the Philippine Mobile Belt and is gradually disappearing. The greatest relief amplitudes occur near the plate boundaries: deep ocean trenches are associated with subduction zones and mountain ranges with collision belts. The landforms of the more stable areas of the plates date back to a more remote past and, where emerged, have a more subdued relief that is in the first place related to the resistance of the rocks to humid tropical weathering Rising mountain ranges and emerging island arcs are subjected to rapid humid-tropical river erosions and mass movements. The erosion products accumulate in adjacent sedimentary basins where their increasing weight causes subsidence by gravity and isostatic compensations. Living and raised coral reefs, volcanoes, and fault scarps are important geomorphic indicators of active plate tectonics. Compartmental faults may strongly affect island arcs stretching perpendicular to the plate movement. This is the case on Java. Transcurrent faults and related pull-apart basins are a leading factor where plates meet at an angle, such as on Sumatra. The most complicated situation exists near the triple-junction and in the Moluccas. Modern research methods, such as GPS measurements of plate movements and absolute dating of volcanic outbursts and raised coral reefs are important tools. The mega-landforms resulting from the collision of India with the Asian continent, around 50.0 my. ago, and the final collision of Australia with the Pacific, about 5.0 my. ago, also had an important impact on geomorphologic processes and the natural environment of SE-Asia through changes of the monsoonal wind system in the region and of the oceanic thermo-haline circulation in eastern Indonesia between the Pacific and the Indian ocean. In addition the landforms of the region were, of course, affected by the Quaternary global climatic fluctuations and sea level changes.